Efficacy of Electroacupuncture on Treating Depression-Related Insomnia: A Randomized Controlled Trial - Yin X (Dove Medical Press, 2020)
Xuan Yin,1,* Wei Li,1,2,* Huangan Wu,3,* Bo Dong,1 Jie Ma,1 Shanshan Li,1 Lixing Lao,4,5 Shifen Xu1 1Department of Acupuncture and Moxibustion, Shanghai Municipal Hospital of Traditional Chinese Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, 200071, People’s Republic of China; 2School of Basic Medicine, Guangzhou University of Chinese Medicine, Guangzhou, 510006, People’s Republic of China; 3Shanghai Research Institute of Acupuncture and Meridian, Shanghai University of Traditional Chinese Medicine, Shanghai, 200003, People’s Republic of China; 4School of Chinese Medicine, The University of Hong Kong, Hong Kong; 5Virginia University of Integrative Medicine, Fairfax, VA 22031, USA*These authors contributed equally to this workCorrespondence: Shifen Xu; Lixing Lao Email xu_teacher2006@126.com; llao@vuim.eduObjective: To evaluate the efficacy of electroacupuncture (EA) on treating insomnia in patients with depression.Patients and Methods: In a patient-assessor-blind, randomized and sham controlled trial, 90 depression patients with insomnia were assigned into three different groups, receiving EA in the treatment group, superficial acupuncture at sham points in the control group A, or Streitberger non-insertion sham acupuncture in the control group B. Treatment was applied 3 times weekly for 8 consecutive weeks. The primary outcome was measured using the Pittsburgh Sleep Quality Index (PSQI). Secondary outcomes were sleep parameters including sleep efficiency (SE), total sleep time (TST) and numbers of sleep awakenings (SA) recorded in the actigraphy, as well as applying the Hamilton Rating Scale for Depression (HAMD-17), Self-Rating Depression Scale (SDS) and Hamilton Rating Scale for Anxiety (HAMA). Assessments were performed at the baseline (week 0), week 4, week 8, and week 12. Linear mixed-effects models were used for analyses and all statistical tests were two-sided.Results: Patients in the EA group had more significant improvement in PSQI scores than those in the control groups over time (respectively p< 0.001 and p=0.04 for treatment and time interaction). At 8-week posttreatment, the EA group reported a reduction of − 6.64 points in PSQI scores compared with − 2.23 points in the control group A (95% CI= − 5.74 to − 2.39) and − 2.94 points in the control group B (95% CI= − 5.73 to − 2.47). Compared with the two control groups, significant between-group differences were seen in SE (both p< 0.01) and TST (both p< 0.01) at week 8; similar results can be found in HAMD-17, SDS, and HAMA scores as well. However, there were no between-group differences in SA (respectively p=0.24 and p=0.08) after 8-weeks of treatment.Conclusion: Electroacupuncture may improve the sleep quality of patients with depression.Trial Registration: Chinese Clinical Trial Registry (ChiCTR); URL: http://www.chictr.org.cn/showproj.aspx?proj=12327; Trial ID: ChiCTR-IIR-16008058.Keywords: insomnia, depression, electroacupuncture, randomized controlled trial